Fases de investigação geológico-geotécnica para a implantação de dutovias - Sargentini, Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The research addresses the need for detailed geological and geotechnical investigations in pipeline’s design, given the diversity of geological units crossed by these works along its layout, which often extends for hundreds of miles. For its large size, this type of work often goes through different states and regions with very different characteristics in terms of topography, vegetation, geology and geotechnical conditions. For a better use of these investigations in order to avoid unnecessary costs and inefficient results, some authors recommend that steps be taken to study, seeking a progressive detail of the pipeline’s implantation area. The main objective of the study is to describe, analyze and correlate the proposals for geological and geotechnical’s investigation recommended by the authors selected. Nogueira Junior & Marques (1998) suggest that for better effectiveness of geological and geotechnical investigations associated with the deployment of pipelines, different research methods are applied sequentially in five major stages of the building. Rocha et al (2008) recommend that, for the pipeline’s implantation using horizontal directional drilling, investigations are performed in three phases of study, to be developed in coordination with the project stages. For Gelinas & Mathy (2004), when time and budget constraints permit, geotechnical investigations for directional drilling projects for pipelines must be made in four sequential phases. Heinz (2008) suggests that the geotechnical investigations for pipeline’s implantation using horizontal directional drilling at crossings of water bodies are carried out in three successive stages. By the development of research, we could see that all the different proposals recommend studies in sequential phases, starting from a more general scale for a more specific, seeking a progressive understanding of the geological model of the area where you intend to deploy the pipeline

A pesquisa aborda a necessidade de investigações geológico-geotécnicas detalhadas no projeto de dutovias, dada a diversidade de unidades geológicas atravessadas por estas obras ao longo de seu traçado, que muitas vezes se estende por centenas de quilômetros. Por sua grande extensão, este tipo de obra atravessa frequentemente estados e regiões diferentes, com características bem distintas em termos de relevo, vegetação, geologia e condições geotécnicas. Para um melhor aproveitamento dessas investigações, a fim de evitar gastos desnecessários e resultados ineficientes, alguns autores recomendam que sejam realizadas fases de estudo, buscando um detalhamento progressivo da área de implantação da dutovia. O objetivo principal do trabalho é descrever, analisar e correlacionar as diferentes propostas de investigações geológico-geotécnicas recomendadas pelos autores selecionados. Nogueira Júnior & Marques (1998) sugerem que para uma maior eficácia das investigações geológico-geotécnicas associadas à implantação de dutovias, diferentes métodos de investigação sejam aplicados sequencialmente em cinco grandes fases da obra. Rocha et al (2008) recomendam que, para implantação de dutovias utilizando perfuração direcional dirigida, as investigações sejam realizadas em três fases de estudo, a serem desenvolvidas de forma coordenada com as etapas do projeto. Para Gelinas & Mathy (2004), quando as restrições de tempo e orçamento permitirem, as investigações geotécnicas para projetos de perfuração direcional para dutovias devem ser feitas em quatro fases sequenciais. Heinz (2008) sugere que as investigações geotécnicas para implantação de tubulações utilizando a técnica de perfuração direcional dirigida em travessias de corpos d’água sejam efetuadas em três estágios sucessivos. Através do desenvolvimento da pesquisa, pôde-se visualizar... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geologia de engenharia; Petroleo - Transporte; Mecanica do solo; Engineering geology; Petroleum - Transportation; Soil mechanics